The New Ten : Zeitgenössische Kunst aus den 10 neuen Mitgliedsstaaten der Europäische Union = Contemporary Art from the 10 new Member Nations of the European Union. - Hegyi, Lóránd; Jurenaite, Raminta; Pleitgen, Fritz; Smerling, Walter; Weiss, Evelyn; Exhibition. The New Ten : Zeitgenössische Kunst aus den 10 neuen Mitgliedsstaaten der Europäischen Union. MKM (Museum Küppersmühle für Moderne Kunst) Duisburg. 2004-07-04. 2004-09-05 (Bonn Duisburg : MKM (Museum Küppersmühle für Moderne Kunst) Duisburg Stiftung für Kunst und Kultur e.V. Bonn, 2004)
The community of European nations has grown. We can only get to know each other by engaging in an intensive dialogue. Art and culture are important foundations for mutual understanding. The New Ten is an exhibition displaying the work of 20 artists from the 10 new EU Member States that is intended to help us gain insight into and understand each other in a language we all understand. The initiators of the exhibition perceive art as a constructive opportunity for fostering integration.
Ole, Kaido ; Semper, Ene-Liis ; Famous Five ; Kursisa, Kristine ; Jankus, Karolis ; Mazuras, Petras ; Borg, Trevor ; Clark, James Vella ; Jozefowicz, Katarzyna ; Sawicka, Jadwiga ; Hostinak, Bohdan ; Krén, Matej ; Bernik, Viktor ; Zidar, Dusan ; Kafka, Ivan ; Vincourova, Katerina ; Lakner, Antal ; Szépfalvi, Agnes ; Loizidou, Maria ; Theodoulos
biog., ind. tent., gr. tent. per kunstenaar
Duits
Engels
boek
Keywords: Cyprus; Estland; Europa; Hongarije; Letland; Litouwen; Malta; Polen; Slovakije; Slovenië; Tsjechië